Hot isostatic pressing of potassium-magnesium-phosphate materials for cesium immobilization - Sayenko, S.Y.; Shkuropatenko, V.A.; Kholomeev, G.O.; Pylypenko, O.V.; Zykova, A.V.; Belash, M.M.; Tarasov, R.V.; Surkov, O.Y.; Ulybkina, E.A.; Lobach, K.V.; Sawczak, M.; Kmiec, M. (Functional Materials, 2018)
High-density potassium-magnesium phosphates (PMP), produced by hot isostatic pressing (HIP) at temperature of 900°C and pressures of 200 and 400 MPa, are promising materials for the immobilization of radioactive cesium. The maximum density of PMP samples was obtained after HIP at pressure of 400 MPa, 900° and holding time of 1 h, and PMP + 10 wt. % CsCl samples at 200 MPa, 900° and 1 h. The resulted materials possess monophase monoclinic structure of potassium-magnesium monophosphate α-KMgPO₄. The possibility of PMP materials to incorporate cesium into its structure by substitution with potassium has been studied by X-ray phase analysis and laser mass spectrometry methods using. The homogeneous fine-crystalline structure of ceramic PMP and PMP + 10 wt.% CsCl samples after HIP was analyzed by scanning electron microscopy method.